Analysis of the Risk Factors for Hypotension in Laparoscopic Hiatal Hernia Repair - Jin YN; Feng H; Wang ZY; Li J (International Journal of General Medicine, 2021)
Ya-Nan Jin, Hao Feng, Zhen-Yuan Wang, Jie Li Department of Anesthesiology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Jie LiDepartment of Anesthesiology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of ChinaTel +86 13621288322Fax +86 10 51718475Email lijie1988@email.cnObjective: This study aimed to investigate the risk factors for hypotension in patients undergoing laparoscopic hiatal hernia repair.Methods: The clinical data of patients who underwent laparoscopic repair of a hiatal hernia in the Beijing Chao-Yang Hospital of Capital Medical University between February 2018 and January 2021 were retrospectively collected, and their perioperative data were obtained by querying the electronic medical record system. The patients were divided into two groups—a hypotension group and a normal group—based on the occurrence of intraoperative hypotension, which was defined as a mean arterial pressure < 65 mmHg and lasting ≥ 1 minute during the operation. The variables with a P value ≤ 0.1 in univariate regression analysis and clinically considered relevant variables were included in multivariate regression analysis in order to screen the risk factors for hypotension in these patients.Results: A total of 114 patients were included in the analysis. The incidence of hypotension was 54.4%. Old age was identified as the only risk factor for hypotension during hiatal hernia surgery.Conclusion: Old age is the only risk factor for intraoperative hypotension in patients undergoing laparoscopic hiatal hernia repair.Keywords: hiatal hernia, hypotension, risk factors